2023
DOI: 10.1128/spectrum.00569-23
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities and Inoculum Effects of Cefiderocol and Aztreonam-Avibactam against Metallo-β-Lactamase-Producing Enterobacteriaceae

Abstract: The prevalence of infections caused by carbapenem-resistant Enterobacteriaceae is increasing worldwide. Currently, therapeutic options for metallo-β-lactamase (MBL)-producing Enterobacteriaceae remain limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There have been limited reports on the E. cloacae complex ST316 lineage elsewhere; one study identified nine E. hormaechei ST316 isolates encoding bla KPC-2 in the United Kingdom between 2014 and 2016 as part of a larger reference study, however, the plasmid content was not reported ( 33 ). Otherwise, eight isolates [one each from references ( 34 36 ), and five from reference ( 37 )] of E. hormaechei ST316 have been recently been reported to carry bla NDM-1 in Asia. Although conjugation genes were present, the narrow host range of the plasmid suggests that bla KPC persistence is likely due to the ST316 clone and not driven by the plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…There have been limited reports on the E. cloacae complex ST316 lineage elsewhere; one study identified nine E. hormaechei ST316 isolates encoding bla KPC-2 in the United Kingdom between 2014 and 2016 as part of a larger reference study, however, the plasmid content was not reported ( 33 ). Otherwise, eight isolates [one each from references ( 34 36 ), and five from reference ( 37 )] of E. hormaechei ST316 have been recently been reported to carry bla NDM-1 in Asia. Although conjugation genes were present, the narrow host range of the plasmid suggests that bla KPC persistence is likely due to the ST316 clone and not driven by the plasmid.…”
Section: Discussionmentioning
confidence: 99%